Cloud Computing and The Future of Higher Education Institutions - Mokhtar, Bekkari (Journal of Economic, Administrative and Legal Sciences, 2024)
The aim of this research is to elucidate the challenges facing higher education institutions in the era of cloud computing. This is done by explaining the integrated philosophy of cloud computing in terms of its concept, origin, evolution, characteristics, and types, as well as the various services it provides to individuals and educational institutions. The goal is to achieve its objectives and fulfill its functions, and then develop a future vision for the potential benefits of cloud computing services. To achieve the research objectives, the researcher utilized a descriptive methodology in the theoretical aspect by presenting the historical development of cloud computing. Additionally, an analytical approach was followed to analyze the model of cloud computing and its application requirements in higher education institutions in the context of the Fourth Industrial Revolution, encompassing information technology, artificial intelligence, and the Internet of Things. The study findings demonstrate that the use of cloud computing by universities contributes to guiding students towards positively leveraging the digitization factor, which has become their primary concern. It also helps attract students and enhance their intrinsic motivation towards knowledge and learning. Moreover, the application of cloud computing technology in educational institutions brings numerous benefits, including access to file storage, email services, databases, educational resources, applications, and research tools from anywhere, thereby making them available to students, teachers, faculty members, graduates, and staff of those institutions. Based on the study results, the research recommends the need for senior management to stay informed about the latest developments in cloud computing technologies and their importance. It emphasizes the importance of providing legal protection in the use of cloud computing, establishing plans for information protection and confidentiality due to the adoption of cloud computing, ensuring the availability of advanced and suitable equipment and facilities to deliver educational services, and promoting the selection of flexible systems that can accommodate any changes required by cloud computing adoption.